Allogeneic hematopoietic stem cell transplant for familial hemophagocytic lymphohistiocytosis: a case report and literature review - Bingjie, Liu; Linlin, Zhang; Futian, Ma; Fan, Xuan; Huan, Du; Wu, Xiaoli; Zhou, Lixia; Fuxu, Wang; Xuejun, Zhang; Ying, Wang (Frontiers in Immunology, 2024)
Abstract Objective: This study aims to discuss the clinical manifestations and treatment of Familial hemophagocytic lymphohistiocytosis (FHL) caused by a mutation in the UNC13D gene. Methods: A 6-year-old female child presented with unexplained febricity, splenomegaly, pancytopenia, hemophagocytic lymphohistiocytosis in bone marrow, decreased NK cell activity, soluble CD25 levels > 44000ng/ml. Genetic sequencing revealed a mutation in the UNC13D gene. Additionally, the patient experienced intermittent fever with seizures characterized by involuntary twitching of the left upper limb. Head magnetic resonance imaging (MRI) showed white matter lesions. Results: According to the HLH-2004 diagnostic criteria revised by the International Society of Histiocytosis the patient was diagnosed with FHL. Despite receiving HLH-2004 treatment, the disease relapsed. However, after a salvage allogeneic Hematopoietic Stem Cell Transplant (HSCT), febricity, abnormal blood cells, and neurological symptoms significantly improved. Conclusion: Prompt performance of allogeneic HSCT is crucial upon diagnosis of FHL, especially when neurological involvement is present.